Analysis Of The General State Of Music Education In A Secondary School - Rasulova Saida Sabirovna (Genius Journals, 2021)
The issues of musical education at school are inextricably linked with the problem of cognitive interest, since it is known that modern schoolchildren, especially teenage schoolchildren, perceive serious classical art ambiguously. Actively interested in any aesthetic activity (in preschool and primary school age), schoolchildren later often lose interest in music lessons and in the most serious music.
Keywords: Complex music lessons; history and theory of performance; psychology of musical perception; criticism